MOBILITAS MAHASISWA INDONESIA DI BELANDA INDONESIAN STUDENTS MOBILITY IN THE NETHERLANDS - Choerunisa Noor Syahid (Research Center for Regional Resources-Indonesian Institute of Sciences (P2SDR-LIPI), 2015)
Today the student mobility becomes an important issue in the global dynamics. As a student, they have good qualifiation with their high level of education, and at the same time their access to the international labor market also open wider. However, on the other hand, based on the resources and networks that they have, they also have many opportunities to engage in the public activities, which related to social and political issues, both in their own fatherland or as a part of the world. Based on those both domain, by using historical and sociological approach, this study will observe the personal and structural aspects of the Indonesian students mobility in the Netherlands.Keywords: mobility, Indonesian students, higher education, the Netherlands